LAMACCA: Learning Analytics–Driven Adaptive Modular LMS Architecture for Collaborative Cyber Classrooms in Higher Education - Rahmaniar; Sapto Haryoko; Muhammad Rais; Supriadi (Journal of Vocational, Informatics and Computer Education, 2025)
This study addresses limitations of many Learning Management Systems (LMS) that operate primarily as content management and administrative platforms with minimal integration of learning analytics, adaptive learning, and collaborative cyber classroom environments. Despite advances in artificial intelligence, educational data mining, and immersive technologies, these components are often implemented as separate tools rather than parts of an integrated system. This fragmentation limits the ability of institutions to transform LMS into intelligent learning ecosystems that are data informed, adaptive, modular, and collaborative. This study aims to propose LAMACCA (Learning Analytics–Driven Adaptive Modular LMS Architecture for Collaborative Cyber Classroom) as a conceptual framework that integrates learning analytics, adaptive mechanisms, modular learning design, and collaborative cyber classroom interaction into a unified LMS architecture capable of supporting data informed pedagogy in higher education. A conceptual research design was conducted through systematic literature synthesis across four domains: learning analytics, adaptive learning systems, modular architectures, and collaborative virtual learning environments. Studies were examined using criteria of architectural relevance, pedagogical alignment, and cyber classroom integration to identify core principles and model their integration into a unified LMS structure. The study produces a four layer architectural model consisting of (1) a learning analytics engine as the intelligence core, (2) adaptive mechanisms for personalized learning pathways, (3) modular learning components for flexible instructional design, and (4) a collaborative cyber classroom environment that enables real time interaction supported by analytics based monitoring. This integration reconceptualizes the LMS from a passive content management platform into an adaptive, collaborative, and analytics driven cyber learning ecosystem.